Профилактика и лечение ишемической болезни сердца на врачебном участке - Кузько Николай Васильевич (Здоров'я, 1985)
Экземпляры: КХ (20210305) / Инвентарный номер: 861137 / Сис.шифр: 616.1 / Авт.знак: К 89 / ГРНТИ: 76 / ББК: 5